Women Leadership Paradigm: Pro and Contra on Women as Leaders in Various Views - Sugiyanto, Eviatiwi Kusumaningtyas (Economics and Business Solutions Journal, 2020)
The number of female workers is increasing and its role in leadership is giving its own perspective on the topic of women leadership. Pro and contra phenomenon related to women leadership still exist in the society. In addition to explain the paradigm of woman leadership, this study also explains the pro and contra of women leadership from various perspectives and provides an overview of how the pro and contra emerge. The method that was used in this study is literature study from the Al-Quran, books, journals and studies. The findings of this study shows that women leadership style leads to transformational, democratic, collaborative styles and have high relational value. Leadership is left to follow one's worth and ability from either men or women. If someone meets the requirements and deserves to be a leader even though from the women's group this remains true. The emergence of pro and contra is based on different point of views; every point of view has different concepts which lead to different practices. The results of an interpretation are not only come from the methods and approaches used, but are also influenced by their socio-cultural and ideological conditions.